Improving Students’ Reading Comprehension Through Mind Mapping - Khoirul Wafa; Alif Yuanita Kartini; Ms. Ahmad Tauchid; Ifa Afiana (STAI Miftahul Ula Nganjuk, 2018)
This research aimed to determine the use of the mind map technique in teaching reading comprehension in the 8th grade of Assalam Bangilan. This research is related to the result of a preliminary study showed that the students were still confused to comprehend the passage in reading skill; In conducting this study, the writer used Classroom Action Research (CAR) as the method of the research. She used research design of Kemmis and Mc Taggart which consisted of two cycles and each cycle consisted of four phases, they are Planning, Acting, Observing and Reflecting. To collect and analyze the data, the researcher gained the information from the questionnaire, documentation and the students’ achievement in pre-test and post-test in order to support the data collected. The result of this research indicated that there was an improvement of students’ scores in reading comprehension through mind mapping technique. It was proved by the data, which showed that the mean of the students in cycle II (93) was higher than in cycle I (70,3) and also in Orientation test (56,3). The writer also analyzed the qualitative data to support these research findings. The qualitative data were taken from a questionnaire sheet and documentation to know how mind mapping technique could improve the students’ ability in reading comprehension. Based on the finding of the research, the writer concluded that mind mapping had improve students’ reading comprehension.